2020
DOI: 10.1021/acssuschemeng.9b07839
|View full text |Cite
|
Sign up to set email alerts
|

High-Titer Glutamic Acid Production from Lignocellulose Using an Engineered Corynebacterium glutamicum with Simultaneous Co-utilization of Xylose and Glucose

Abstract: Xylose utilization by Corynebacterium glutamicum is an essential but unresolved issue in glutamic acid production from lignocellulose biomass. Coexistence of xylose with inhibitors requires a selective removal of inhibitors while the xylose is still well retained in the pretreated lignocellulose feedstock. Not only is xylose assimilation in C. glutamicum at low efficiency, but also there are unique challenges, which eliminate the generation of glutamic acid from xylose when lignocellulose is used. There includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Then H 2 O 2 in PHP solvent system reacted with acetic acid in acidic environment to form peroxyacetic acid, which initiated the selective lignin oxidation and degradation. Peroxyacetic acid then oxidized xylose and lignin to produce more acetic acid [ 48 ], which consequently boosted the peroxyacetic acid formation and biomass deconstruction. Due to the continuous production of peroxyacetic acid, the cyclic synergistic effect of PHP pretreatment was continuously increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Then H 2 O 2 in PHP solvent system reacted with acetic acid in acidic environment to form peroxyacetic acid, which initiated the selective lignin oxidation and degradation. Peroxyacetic acid then oxidized xylose and lignin to produce more acetic acid [ 48 ], which consequently boosted the peroxyacetic acid formation and biomass deconstruction. Due to the continuous production of peroxyacetic acid, the cyclic synergistic effect of PHP pretreatment was continuously increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Successive metabolic engineering related to the glyoxylate shunt was performed with the use of glucose as the sole feedstock Via a nonphosphorylative xylose metabolic pathway in E. coli , , 3,4-DHBA at a concentration of 1.27 g/L was produced from 20 g/L xylose in 51 h …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the model organism C. glutamicum was extensively engineered to broaden its substrate spectrum according to the flexible feedstock concept ( Wendisch et al, 2016 ). Thereby, access to the lignocellulosic pentoses arabinose ( Kawaguchi et al, 2008 ; Schneider et al, 2011 ; Meiswinkel et al, 2013 ) and xylose ( Kawaguchi et al, 2006 ; Jin et al, 2020 ) for growth and production of amino acids was enabled. Recently, it could also be demonstrated that production of sarcosine from the pentose xylose was more efficient than that from glucose ( Mindt et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%